Motivações para a leitura e promoção do acesso a livros: três casos improváveis dos meios populares celebrizados pela mídia - Roberto Cezar de Souza Silva (2015)
Even with the democratization of access to education and the growing profusion of researches addressing readers in popular environments, today it is still somehow surprising to find great readers in these ambiences, chiefly among individuals with professions considered as low qualification. And this is so true that, when it happens, some of these individuals end up by becoming news in media or research subjects. For the present research, three of these celebrated individuals were selected; namely: Luiz Amorim, a butcher; Evando dos Santos, a mason; and Vanilda de Jesus Pereira, a caregiver for elders, former maid/babysitter/paper collector. But it was not only the fact of their having the habit to read books that have made them famous; in addition to that, these individuals have developed projects to promote the access to books, which had great social repercussion and acknowledgement, in their communities, in the cities where they live and beyond. This research analyzed some of the media materials to check how public images of these readers/promoters of books were produced and which would be some of the values/ideologies behind it. Then, data collected from two meetings with each of these individuals, by means of semi-structured interviews, were analyzed. Starting from a sociological theory, that of human motivation which finds in the need of recognition/social support and ontological safety and in the search for emotional energy, the explanation to how individuals deal with social interactions in their lives; data were analyzed in order to rebuilt the possible social processes that generate the valorization, liking and habit of reading and promoting books. It was observed a trend to mystify these social processes and lives of individuals both in media speech and how individuals usually present themselves. It was emphasized the dangers inherent to such mystification to build a critical thinking, for social sciences and for education concerning the formation of readers, since, many times, the reasons that make an individual, under conditions considered unlikely, become a reader are usually explained by individuals gifts or by a magic aura of the book Salvationist by contact alone. It was observed that the reader/promoter of books is formed from a chain of social interactions that, along their lives reward them emotionally, making them more steady, self-confident, and with self-esteem, within a market of interaction in which to be/present oneself as reader is something highly regarded.